Silica-based nanohybrids containing europium complexes covalently grafted: structural, luminescent, and cell labeling investigation - Mutti, Alessandra M. G. [UNESP]; Canisares, Felipe S. M. [UNESP]; Santos, João A. O. [UNESP]; Santos, Bruno C. [UNESP]; Cavalcante, Dalita G. S. M. [UNESP]; Job, Aldo E. [UNESP]; Pires, Ana M. [UNESP]; Lima, Sergio A. M. [UNESP] (Springer Nature, 2023)
Abstract: Designing luminescent nanohybrids for bioimaging proposes has been explored by different approaches in the literature. In this context, here silica luminescent nanohybrids containing Eu3+-complexes were synthesized in three different approaches to determine the better methodology to obtain the most efficient emissive final hybrid and its applicability in cell imaging by using the Eu3+ luminescent probe properties. For this, the synthesized dense Stöber silica nanoparticles, SiO2, had their surface functionalized with APTES, in which its amine group reacted with salicylaldehyde to form a Schiff base ligand (SB), yielding the SiO2-SB system. Then, Eu3+ ion was coordinated to the SB, followed by the displacement of coordinated water molecules by dibenzoylmethane (dbm), resulting in the SiO2-[Eu1] hybrid. SiO2-[Eu2] hybrid, in turn, was obtained from tris-[Eu(dbm)3] complexes coordinated to the imine groups grafted on the SiO2-SB surface. For the third hybrid, SiO2-[Eu3], a new Eu3+-Schiff base complex displaying a triethoxysilyl group was grafted onto the SiO2 surface. The three luminescent hybrids are spheroidal shaped with 100 nm-size and they are red emitters with long lifetime (0.34–0.61 ms) and high photostability when exposed to continuous 340 nm UV radiation. Quantum efficiency (QEuEu) as well as the number of coordinated water molecules (qH2O) to the Eu3+ was estimated using the LUMPAC software package and Horrocks equation, respectively. Although the three strategies exhibited suitable photophysical results, SiO2-[Eu1] was classified as the best hybrid considering its higher QEuEu and color purity values, and it was evaluated as non-toxic according to its bio-viability in CHO-k1 cells in different doses. Exploratory cell imaging tests using such hybrid indicated cell marking near the nucleus with the internalization of nanoparticles in the cell confirmed by Eu3+ (5D0 → 7FJ) narrow emission bands. Therefore, SiO2-[Eu1] hybrid manifested suitable shape and size, optical, and biocompatibility features that make it promising to be applied as a luminescent stain for cell imaging. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Europium complex; Functionalized silica; Luminescent bioimaging; Photoluminescence; Sol–gel